2020
DOI: 10.3389/fpsyg.2020.569035
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Immersed in a Hyper-Realistic Surgical Training Environment Leads to Improved Measures of Emotional Resiliency by Both Hardiness and Emotional Intelligence Evaluation

Abstract: BackgroundBurnout is being experienced by medical students, residents, and practicing physicians at significant rates. Higher levels of Hardiness and Emotional Intelligence may protect individuals against burnout symptoms. Previous studies have shown both Hardiness and Emotional IntelIigence protect against detrimental effects of stress and can be adapted through training; however, there is limited research on how training programs affect both simultaneously. Therefore, the objective of this study was to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Previous studies have identified positive coping strategies and hardiness as buffers against the negative effects of stress in general (Kobasa, 1982 ; Kobasa et al, 1982 ). Hardiness, defined by Kobasa ( 1979 ) as a personality trait consisting of three fundamental characteristics (commitment, control and challenge), is a protective factor against the negative effects of stress including burnout (White et al, 2020 ; Bartone et al, 2021 ). Several recent studies have also found that this psychological resource is a significant buffer against the adverse psychological effects of stress related to the COVID pandemic, for Health Care and Emergency workers (Maiorano et al, 2020 ; Vagni et al, 2020a ) and also in the general population (Dymecka et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified positive coping strategies and hardiness as buffers against the negative effects of stress in general (Kobasa, 1982 ; Kobasa et al, 1982 ). Hardiness, defined by Kobasa ( 1979 ) as a personality trait consisting of three fundamental characteristics (commitment, control and challenge), is a protective factor against the negative effects of stress including burnout (White et al, 2020 ; Bartone et al, 2021 ). Several recent studies have also found that this psychological resource is a significant buffer against the adverse psychological effects of stress related to the COVID pandemic, for Health Care and Emergency workers (Maiorano et al, 2020 ; Vagni et al, 2020a ) and also in the general population (Dymecka et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…2017; Kobasa, 1979; White et al. 2020) have demonstrated that better ability to adapt protects against burnout. MEDTHINKER assesses adaptability while concurrently assessing clinical performance and can be used to evaluate the impact of physician burnout on clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 21 articles, 12 met eligibility criteria and were included in the review. [28][29][30][31][32][33][34][35][36][37][38][39] Characteristics of the included studies can be found in Appendix 1. Of the 9 studies that were not included in the review, 3 utilized interventions lasting longer than one standard semester, [8,9,40] 2 were performed on nonnursing/medical students, [10,41] 2 utilized unestablished or unvalidated EI instruments, [42,43] 1 did not report the EI instrument utilized, [44] and 1 did not report any description of the intervention content.…”
Section: Study Selectionmentioning
confidence: 99%